This preview shows page 1. Sign up to view the full content.
Unformatted text preview: i s , i 1 and i ): i s R s i 1 R 1 ir = i 1 R 2 i s R x i ( r + R x + R 2 ) = E i s ( R + R s + R x ) i 1 R iR x = The problem statement further species R 1 = R 2 = R and R = 0, which causes our solution for i to simplify signicantly. It becomes i = E ( R s R x ) 2 rR s + 2 R x R s + R s R + 2 rR x + R x R which is equivalent to the result shown in the problem statement. (b) Examining the numerator of our nal result in part (a), we see that the condition for i = 0 is R s = R x . Since R 1 = R 2 = R , this is equivalent to R x = R s R 2 /R 1 , consistent with the result of Problem 43....
View
Full
Document
This note was uploaded on 11/12/2011 for the course PHYS 2001 taught by Professor Sprunger during the Fall '08 term at LSU.
 Fall '08
 SPRUNGER
 Physics, Current, Resistance

Click to edit the document details